Phytochemical analysis and evaluation antibacterial activity of Citrus medica peel and juice growing in Kurdistan/Iraq - Aveen Nozad Adham (Journal of Applied Pharmaceutical Science, 2015)
Citrus medica is an important medicinal plant of the family Rutaceae Qualitative and quantitative screening were performed for evaluation bioactive constituents in Citrus medica fruit. The antibacterial activity of the ethyl acetate and ethanol 80% peel extracts and juice of Citrus medica was assessed by agar well diffusion assay, minimum inhibitory concentration (MIC) value determination by 96 well serial dilution against five gram positive and two gram negative bacteria, while minimum bactericidal concentration (MBC) evaluated by plate cultures. Qualitative investigation shows the presence of carbohydrates, flavonoids, phenols, tannins, steroids, cardioactive glycosides in peel and juice, while saponins, terpenoids, and anthraquinones absent in all fraction of Citrus medica. On quantitative screening peel contain highest quantity tannin as compared to juice while juice contain higher quantity phenol and Citrus medica fruits contain high quantity phenol than flavonoids. The juice of Citrus medica exhibited largest inhibition zone (12mm) at (100mg/ml) and recorded the lowest MIC and MBC value (1.5625mg/ml & 3.125mg/ml) against Staphylococcus auricularis. The ethyl acetate extract of peel revealed antibacterial activity against four bacterial strain while ethanol 80% only against two bacteria. Peel extracts exhibited largest inhibition zone (10 & 22mm) at (100mg/ml) and recorded the lowest MIC value (25mg/ml & 12.5mg/ml) and MBC (50 mg/ml) against Escherichia coli.
Keywords: Citrus medica, phytochemical screening, antibacterial activity, MIC, MBC.